Gastric Cancer Screening Program: A Literature Overview - Vilkelytė, Kamilė; Dulskas, Audrius (Lietuvos chirurgija, 2025)
Objective. To analyze the causes and consequences of global gastric cancer prevalence and justify the need for a preventive program in Lithuania. Methods. Data for the study was gathered from the PubMed database, articles and scientific papers from Vilnius University (VU) electronic database, and printed literature on gastric cancer. The selection included publications meeting the inclusion criteria: full-text accessibility, publication date within the last 10 years, adult population as the study subject, and examination of gastric cancer prevention methods. Results. The literature review included 50 articles addressing gastric cancer prevention. The search utilized the keyword combination: “gastric cancer AND prevention”. The findings indicate that gastric cancer is often diagnosed at advanced stages, limiting treatment options. Lithuania remains among the European countries with the highest incidence and mortality rates of gastric cancer. Factors influencing prevalence include genetic and environmental factors such as an unbalanced diet, smoking, Helicobacter pylori infections, and low public awareness of risk factors associated with the disease. Stratification based on specific risk factors is recommended for identifying high-risk groups. Commonly discussed serological markers include pepsinogen, Helicobacter pylori antibodies, gastrin, ghrelin, urinary markers, and new molecular biological markers. The most significant methods remain invasive techniques such as endoscopy and endoscopy with biopsy and histological examination. Conclusions. Implementing a gastric cancer prevention program would enable early identification of high-risk groups, active patient monitoring, timely disease diagnosis, and reduced healthcare system costs. It is recommended to consider including a gastric cancer screening program in the list of Lithuania’s national preventive programs, promoting public health initiatives, and enhancing the competencies of primary healthcare specialists to ensure early diagnosis and effective patient monitoring.
Keywords: gastric cancer; stomach cancer prevention; screening programs